Cavity enhanced detection methods for probing the dynamics of spin correlated radical pairs in solution - Neil, S; Maeda, K; Henbest, K; Goez, M; Hemmens, R; Timmel, C; Mackenzie, S (2010)
Cavity enhanced absorption spectroscopy (CEAS) combined with phase-sensitive detection is employed to study the effects of static magnetic fields on radical recombination reactions. The chemical system comprises the photochemically generated thionine semiquinone radical and a 1,4-diazabicyclo[2.2.2]octane (DABCO) cationic radical in a micellar solution of sodium dodecyl sulphate. Data obtained using the modulated CEAS technique, describing the magnetic field effect (MFE) on reaction yields, are shown to be superior to those obtained using conventional transient absorption (TA) flash photolysis methods typically employed for these measurements. The high sensitivity afforded by modulated CEAS detection is discussed in terms of the new possibilities it offers such as the measurement of magnetic field effects in real biological systems which have hitherto been largely beyond the detection capabilities of existing techniques. © 2010 Taylor and Francis.